The temperature in the drilling of ex-vivo bovine femurs and human cadaveric tibiae - Fernandes, M.G.A. (2018)
In an ageing society it’s inevitable that the bone fractures occur with increasing frequency. Usually, the fracture treatment involves bone drilling for screw insertion to fix the fractured parts for immobilization. However, high rotational speeds may cause a high rise in bone temperature. It is generally agreed that temperatures above 55°C for a period longer than 30 seconds are deleterious to the bone tissue and leads to the irreversible death of cells. Decrease the heat generation has a great demand as it helps in better fixation and healing of bone tissue.